“CREATIVE ADOBE DESIGN” FLIP BOOK-BASED TEACHING MODULES IN INTERACTIVE MULTIMEDIA - Kholisho, Yosi Nur; Marfuatun; Kholida Ismatulloh (Educate : Jurnal Teknologi Pendidikan, 2023)
At the higher education level, several lecturers still apply hybrid learning so that the learning process can run smoothly and the material is absorbed. Developments and advances in technology in the field of multimedia demand that teaching materials in interactive multimedia courses continue to be updated to keep up with user demands; therefore, it is necessary to update teaching materials. The aims of this study are 1) to design flip book-based teaching modules, 2) to test the feasibility, and 3) to seek user response. The development research method was used in this study by applying the ADDIE model, and the subject consisted of 2 expert judgments in the media field, two expert judgments in the material field, and 15 respondents who came from students. Data collection techniques were carried out through interviews and questionnaires. Based on the feasibility assessment by material experts, an average of 86.25% was obtained in the very feasible category, due diligence by media experts obtained a result of 82.5% in the very feasible category, and based on responses from users, an average of 92.2% was obtained in the very high category. This shows that this interactive multimedia teaching module can foster learning motivation and make it easier for students to understand interactive multimedia material, and it can help students in making interactive multimedia products